Pengembangan Bahan Ajar LKPD Berbasis Software Liveworksheet pada Materi PPKn Fase B di MI/SD - Idris, Imas Yuningsih; Rafani, Indana Zulfa; Latip, Asep Ediana (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
This research was motivated by the lack of educator innovation in developing interactive teaching materials. This can be seen from various phenomena of student saturation related to learning that tends to be boring. The purpose of this study is so that researchers or readers can find out one of the learning innovations that can be used by educators, namely the development of LKPD teaching materials based on Liveworksheet software. The research method used is the Research and Development (R & D) research method with its development model, namely ADDIE (Analyziz, Design, Development, Implementation and Evaluation). At the validation stage, the LKPD was validated by 3 validators, namely 1 material expert validator, 1 linguist validator and 1 design expert validator. The results showed that the development of LKPD teaching materials based on Liveworksheet Software is feasible to be used in learning. This is evidenced by the average V results obtained from material expert validation which is 0.92, linguist validation is 0.75, and design expert validation is 0.96. With the conclusion that LKPD based on Liveworksheet Software is feasible and effective to be used in the learning process in Phase B PPKn Material in MI / SD.